2008
DOI: 10.1007/s10695-008-9210-9
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of benzo[a]pyrene on liver phase I and II enzymes, and DNA damage on sea bream Sparus aurata

Abstract: In the present study biotransformation and detoxification responses to acute exposure to the polycyclic aromatic hydrocarbons benzo[a]pyrene (B[a]P) were investigated in the liver of Sparus aurata (sea bream). Sexually immature gilthead sea bream were treated by intraperitoneal injection of B[a]P (20 mg kg(-1)) for 6, 12, 24, and 48 h. B[a]P accumulation was quantified in sea bream liver by mean of gas phase chromatography (GPC-MS) after the various exposure periods. The following biological responses were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 35 publications
2
15
0
1
Order By: Relevance
“…On the contrary, the data showed a pronounced Phase I biotrasformation, measured as EROD activity, when liver B[a]P uptake was minimal (after 24 h) suggesting a maximum B[a]P liver metabolism after only 24 h. Such results demonstrate a strong liver induction of Phase I enzymes (mediated by cytochrome P450-dependent monooxygenases) involved in the metabolism of B[a]P. Since their activity is evident only few hours after the exposure and reaches the plateau within 24 h (Banni et al, 2009). The early activation hepatic enzymes in sea bream after B[a]P treatment is also confirmed in other in vivo studies (Viarengo et al,1997;Gravato and Santos, 2002).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…On the contrary, the data showed a pronounced Phase I biotrasformation, measured as EROD activity, when liver B[a]P uptake was minimal (after 24 h) suggesting a maximum B[a]P liver metabolism after only 24 h. Such results demonstrate a strong liver induction of Phase I enzymes (mediated by cytochrome P450-dependent monooxygenases) involved in the metabolism of B[a]P. Since their activity is evident only few hours after the exposure and reaches the plateau within 24 h (Banni et al, 2009). The early activation hepatic enzymes in sea bream after B[a]P treatment is also confirmed in other in vivo studies (Viarengo et al,1997;Gravato and Santos, 2002).…”
Section: Discussionmentioning
confidence: 79%
“…Particularly, cells treatment with the highest concentrations of B[a]P led to a significant cell death for primary necrosis within 24 h. This early lethal effect agrees with the B[a]P metabolism studied in vivo in Teleosts by several authors. Banni et al(2009) found that liver uptake of B[a]P after intraperitoneal injection of S. aurata shows a bifasic behaviour reaching the maximum level after 6 h, followed by a decreasing phase till 24 h and a subsequent new increase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are supported by previous studies on other species, treated by different intraperitoneal PAHs injections. Benzo(a)pyrene displayed strong liver EROD and GST induction potency in S. aurata (Banni et al 2008). Phenanthrene was found to induce a concentration-dependant formation of the enzyme EROD in the tilapia, Oreochromis mossambicus.…”
Section: Resultsmentioning
confidence: 93%
“…The use of IP injections to expose aquatic animals to chemical pollutants is a common approach in ecotoxicological investigations (Banni et al, 2009;Nacci et al, 2002;Nahrgang et al, 2009;Padrós et al, 2003;Wang et al, 2006Wang et al, , 2008. A previous study of our research group (unpublished data) showed that intra-peritoneal injection of radiolabelled 14 C-BaP and 113 Sn-TBT in Fundulus heteroclitus did not differ from dietary exposure in regard to tissue distribution of the contaminants.…”
Section: Experimental Designmentioning
confidence: 90%